Medical student mental health: Dialogues between contexts and social determinants from the perspective of Family Medicine (Research, Society and Development, 2024)
The medical student training process within medical schools is full of striking transition phrases, increasing the student's level of anxiety and constant need for readaptation, seeking a sense of belonging in an environment, within social groups, and especially by the intrinsic search to complete steps and acquire skills and abilities necessary for the objective of being successful in a current academic environment and the successful idealization of the glorious imaginary figure of the trained doctor. This study aims to present a critical analysis of concepts inherent to the theme of medical student mental health from the perspective of discussion with an experience report from a family and community medicine resident helping to contribute to preceptorship and teaching activities for students. of medicine in the basic and clinical cycles of a medical school in the countryside of São Paulo State. The report is associated with a reflective narrative review of the topic. It appears that it is essential to have a greater expansion of the work of family and community medicine in creating forms of support and monitoring for undergraduate students, from a person-centered and comprehensive approach perspective, capable of identifying and treating health problems mental health caused by the high impact of social determinants present in the medical course on the student's physical and also mental health, in an integrative vision.